Leading minds : an anatomy of leadership - Gardner, Howard; Laskin, Emma. (New York, NY : BasicBooks, 1996)
Links the study of creativity and leadership to discover the qualities that make a person emerge as a leader in a non-specific domain, identifying six constant features of leadership.
Includes bibliographical references (p. [367]-380) and indexes.
Adult
Keywords: Leadership; Leadership -- Case studies; Leadership; Leadership -- Case studies